Correlation between Reflux Symptom Index and Reflux Finding Score in Laryngopharyngeal Reflux - Sharma, Anshu; Paudel, Dhundi Raj (Journal of Nepalgunj Medical College, 2021)
Introduction: Laryngopharyngeal reflux is an extra esophageal variant of gastro esophageal reflux disease and is characterized by change in voice, recurrent throat clearing, chronic cough, discomfort in throat, globus. The larynx and pharynx are devoid of the normal acid clearance mechanism even three episodes of reflux per week seems to be associated with a significant disease. Aims: The aim of the study was to evaluate the correlation between the reflux symptom index and reflux finding score in patients with Laryngopharyngeal reflux. Methods: This prospective analytical study was conducted from November 2019 to October 2020 in total of 65 patients presented in department of Otorhinolaryngology, Nepalgunj Medcial College and Teaching Hospital, Nepalgunj. Reflux symptom index questionnaire with nine Questions were answered by patients on a 5 point scale. Reflux symptom index of more than 13 out of total score of 45 was considered to indicate Laryngopharyngeal reflux were as, reflux finding score was based on laryngoscopic findings after evaluating 8 items. Score more than 7 out of 26 was taken as an indicator for presence of Laryngopharyngeal reflux. Results: The reflux symptom index was more than 13 on 22 patients withmean11.85±3.48 and reflux finding score was more than 7 on 11 patients with mean 5.02±3.23 with statistically moderate correlation between reflux symptom index and reflux finding score (p=0.000,r=0.595). Conclusion: There is moderate correlation between the reflux symptom index and reflux finding score. The combined use of these questionnaires and laryngoscopic findings can be more precise, practical and cost effective in the diagnosis of laryngopharyngeal reflux.